Analisis Penyebab Cacat Produk Santan Kemasan dalam Penetapan Critical Control Point dengan Pendekatan HACCP di PT. X - Putri, Gustiarini Rika; Senjawati, Maria Isfus; Erlinanto, Yovi (Politeknik ATI Padang, 2020)
Hazard Analysis Critical Control Point (HACCP) ia a quality control system from the preparation of raw maerials to the product and accepted by consumers. HACCP is a requirement for guaranteeing the safety of food products produced according to company quality standards. PT. X produces packaged coconut milk as one of the main products and has implemented HACCP in every production process of its products. The packaged coconut milk that is produced often gets bloated in the finished product warehouse before the product is distributed. Therefore it is necessary to analyze the application of HACCP in the production of packaged coconut milk. HACCP application in the packaged coconut milk production process has set 4 Critical control points. CCP 1 (UHT Sterilization System & Aseptic Tank), CCP 2 (Filtration 500 micron), CCP 3 (Product Sterilization at 140-148ºC) and CCP 4 (Filling with Astepo Filler Filling Machine). Each Critical Control Point has physical and biological hazards, which must be controlled to ensure food safety. The research objective was to analyze the implementation of HACCP plan for coconut milk products based on SNI No. 01-4852-1998 regarding the HACCP system and analyzing the causes of product defects (bloating) in the determination of the CCP. Based on the analysis of HACCP application and the causes of product defects in packaged coconut milk, product defects due to bloating are not defects in the production process but defects caused by cross-contamination of microbes after filling. Cross contamination occurs due to cracks in the neck of the aseptic bag cup that cannot be detected directly, and the use of tools that should not be used during the filling process.